A new and practical surgical technique of transvaginal natural orifice specimen extraction surgery (NOSES) in laparoscopic nephroureterectomy—an initial clinical experience. Issue 7 (16th July 2021) - Zhao, Qinxin; Yang, Feiya; Wu, Liyuan; Han, Sujun; Xing, Nianzeng
Abstract: Objective: To explore the safety, feasibility and clinical effect of transvaginal natural orifice specimen extraction surgery (NOSES) in 3D laparoscopic nephroureterectomy (LNU) for upper tract urothelial carcinoma (UTUC). Methods: A retrospective analysis was made of 16 female patients who underwent 3D LNU and NOSES in the Department of Urology, Cancer Hospital, Chinese Academy of Medical Sciences from June 2019 to December 2020. The basic clinical data, perioperative related data, perioperative complications, visual analogue pain score (VAS), postoperative scar assessment questionnaire (PSAQ) at 3 months, female pelvic floor dysfunction questionnaire (PFDI‐20) and female sexual function index questionnaire (FSFI) at preoperative and postoperative 3 months were analyzed and evaluated. Results: The surgery was successfully completed in all 16 patients, and none of them was converted to open surgery. No postoperative complications, such as abdominal incision‐related infection. No cases of local recurrence and distant metastasis were observed during follow‐up of 3 to 21 months. The VAS scores at 24 h and 48 h after operation were 2.9 ± 0.7, 1.3 ± 0.6, respectively. PSAQ scores at 3 months after operation were 34.3 ± 3.3. PFDI‐20 scores of women preoperative and postoperative 3 months were 6.25 ± 1.75, 6.3 ± 1.8, respectively, and the difference was not statistically significant ( p  = 0.924). There was no significant difference in FSFI scores between preoperative and postoperative 3 months ( p  = 0.892). Conclusion: Transvaginal NOSES in 3D LNU for UTUC is safe, feasible and practical. The successful development of this technique has laid a solid foundation for further clinical application and promotion.